Analysis of FIFO and Average Methods for Corporate Income Tax Savings (Case Study on a Credit Union in Karanganyar) - Nisita Azzahra; Juliati Juliati (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2025)
This research aims to analyze the comparison of inventory valuation methods at Credit Union X using the FIFO method and the average method to achieve efficiency in Corporate Income Tax (CIT). This research employed a quantitative descriptive method by calculating inventory data from purchase and sales transactions from January to December 2024. The samples used in this study are items with regular purchase demand, namely Wipol Karbol Cemara, Pledge Lemon Pouch, Sania Cooking Oil 1 Liter, and Bay Fresh Strawberry. The results show that tax calculations using the rate from article 31E of the Income Tax Law result in a payable tax of Rp544,440 for the FIFO method and Rp542,354 for the average method. Thus, the application of the average inventory valuation method is considered more efficient in terms of tax savings for the company.